Manuais e História da Ciência: a segunda lei de Newton - Lopes Coelho, Ricardo (História da Ciência e Ensino: construindo interfaces, 2019)
Resumo Aprendemos no liceu e na universidade que a segunda lei de Newton é F=ma. Porém, Newton nunca escreveu a equação. Além disso, não há acordo entre os historiadores da ciência em relação à equação que expressa a segunda lei de Newton. Físicos do séc. XVIII, que citaram e explicaram as leis de Newton, não usaram F=ma. Portanto, se a tese dos manuais contemporâneos fosse correta, teríamos de admitir que todos aqueles físicos interpretaram mal a segunda lei de Newton. Por outro lado, Euler defendeu ter descoberto um novo princípio de mecânica, que é F = ma. Comparando a segunda lei de Newton e o princípio de Euler compreendemos que elas diferem significativamente. Este resultado da pesquisa histórica tem implicações nos problemas conceptuais da mecânica e na resolução de problemas, como iremos ver. Palavras-chave: A segunda lei de Newton; o princípio de Euler; manuais. Abstract We learned at high school and university that Newton’s second law is F=ma. However, Newton never wrote this equation. Furthermore, there is no agreement among historians of science as to the equation that expresses Newton’s second law. 18th century physicists, who quoted and explained Newton’s laws of motion, did not use F=ma. Therefore, if contemporary textbook writers’ claim were correct, we would have to admit that all those physicists misunderstood Newton’s second law. They did not grasp that his law was F=ma. Furthermore, Euler claimed to have discovered a principle of mechanics, which is F=ma. This paper of Euler provides us with the means of clarifying the issue. We can compare Newton’s second law and Euler’s principle with each other and verify whether there are significant differences between both laws. The result is that Newton’s second law is not Euler’s principle. This result of historical research has implications for the conceptual problems of mechanics and problem solving, as we shall see. Keywords: Newton’s second law; Euler’s principle; textbooks.